Nietzsche – Psychologist of Religion - Remedios Ávila Crespo (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
The aim of the following article is to fight some common misconceptions with respect to Nietzsche’s views on religion, and to show that these views are considerbly complex. Starting from the close relation between the human experience of suffering and the need for religion, as pointed out by Eliade, Freud and Schopenhauer, this essay focuses on the continuity between psychology and genealogy in Nietzsche’s analyses of religion and morality, it then responds to the questions about the essence, kinds and limits of the fact of religion, and ends by pointing out the different ontological status of Nietzsche’s principal philosophical positions.